Synthesis of Chalcone Derivatives: Inducing Apoptosis of HepG2 Cells via Regulating Reactive Oxygen Species and Mitochondrial Pathway - Zhu, Hongtian; Tang, Lei; Zhang, Chenghong; Wei, Baochu; Yang, Pingrong; He, Dian; Zheng, Lifang; Zhang, Yang (Frontiers in Pharmacology, 2019)
Chalcone derivatives, as a hot research field, exhibit a variety of physiological bioactivities and target multiple biological receptors. Based on the skeleton of (E)-1,3-diphenyl-2-propene-1-one, 14 chalcone derivatives were designed and synthesized, and evaluated as the antitumor candidates agents against four human cancer cell lines (A549, Hela, HepG2, and HL-60) as well as one normal cell line (WI-38). Among the title compounds, compound a14 showed better inhibitory activity against HepG2 cells (IC50 = 38.33 µM) and had relatively weak cytotoxicity towards normal cells WI-38 (IC50 = 121.29 µM). In this study, apoptosis, cycle arrest, assessment of reactive oxygen species (ROS) level, and measurement of mitochondrial membrane potential were adopted to explore the inhibitory mechanism of a14 towards HepG2. Compound a14 could effectively block the division of HepG2 cell lines in the G2/M phase and robustly induced generation of ROS, demonstrating that the generation of ROS induced by a14 was the main reason for resulting in the apoptosis of HepG2 cells. Moreover, the mitochondrial membrane potential (MMP) of HepG2 cells treated with a14 was significantly decreased, which was closely related to the enhanced ROS level. Furthermore, based on Western blot experiment, cell apoptosis induced by a14 also involved the expression of B-cell lymphoma-2 (Bcl-2) family and Caspase 3 protein. In summary, compound a14 could contribute to the apoptosis of HepG2 cells through regulating ROS-mitochondrial pathway, which provides valuable hints for the discovery of novel anti-tumor drug candidates.